Binge eating and its relationship with food consumption during the pandemic period in women over 50 years old (Research, Society and Development, 2021)
In early 2020, a pandemic called COVID-19 affected the health of the world, as well as eating habits, frequency of food consumption and binge eating were present, giving individuals a false sense of pleasure (with a view to decreasing damage). In moments lived in social isolation, many women found themselves in disharmony with a whirlwind of new feelings, including the effects of entering the climacteric. The present study aimed to analyze binge eating and its relationship with food consumption in women aged 50 years and over during the pandemic. The research was cross-sectional and descriptive, evaluated through questionnaires such as the food frequency questionnaire and binge eating scale, in addition to an adapted questionnaire. The sample consisted of 50 participants (menopause women), where it was found that despite the hormonal change, most of these women are in a state of moderate binge eating, as they are able to control the quantity/quality of food and periodicity. There was an increase in the frequency of consumption of all food groups. Therefore, it is possible to conclude that binge eating in women over 50 years old during the pandemic was considered moderate and that it is due to several factors, including stress, diets. fashion without the guidance of a specialized professional and emotional conditions. And that there has been a considerable increase in frequency and consumption in all food groups.